SOCIAL SIGNIFICANCE OF THEORETICAL AND PRACTICAL BASIS OF PICTURE ACTIVITY IN PRE-SCHOOL EDUCATION - Raxmatova Ikbolxon Inomjonovna; Sodiqova Aziza Sodiqjon qizi (Journal of new century innovations, 2022)
Annotation: In this article, the subject and basic concepts of the science of teaching preschool children to visual activity, the theoretical and practical foundations of visual activity in preschool educational organizations, the issues of developing the skills of aesthetic perception of nature and its phenomena in preparing children for school education are covered.